mph (Dictionary of Mong Njua, 1974)
BACKGROUND: Direct oral anticoagulant (DOACs) use for pediatric venous thromboembolism has increased, yet data on reversal strategies using 4-factor prothrombin complex concentrate (4F-PCC) remains limited. OBSERVATION: We report the first case of intracranial hemorrhage (ICH) in a patient receiving rivaroxaban who underwent reversal with 4F-PCC. An 11-year-old male with sinusitis complicated by multifocal intracranial abscesses, and superior sagittal sinus thrombus treated with rivaroxaban, was found to have ICH. For urgent craniotomy, rivaroxaban was reversed with 2223 units (∼45 units/kg) 4F-PCC. No thromboembolism occurred within 3 months. CONCLUSION: This case adds to the limited literature supporting 4F-PCC for DOAC reversal in pediatrics.